2018
DOI: 10.1093/eurpub/cky113
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet and health outcomes: a systematic meta-review

Abstract: MeDi has been shown to be a healthy dietary pattern that may reduce risk related to NCD. The effect is larger if the pattern is combined with physical activity, and tobacco and excessive alcohol consumption are avoided. Promoting the MeDi as a healthy dietary pattern presents challenges which need the collaboration of all levels of society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 24 publications
1
88
0
2
Order By: Relevance
“…In particular, a number of studies have shown that adoption of a Mediterranean-like dietary pattern [1] improves the health status [2], decreases morbidity and mortality [3] and reduces the total lifetime costs [2]. Benefits have been demonstrated in terms of decreased risk of cardiovascular diseases (CVD) [4][5][6], obesity [7], metabolic syndrome [8,9] and type-2 diabetes [10-13], as well as of certain types of neurodegenerative diseases and late-life cognitive disorders [14-17] and cancers [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a number of studies have shown that adoption of a Mediterranean-like dietary pattern [1] improves the health status [2], decreases morbidity and mortality [3] and reduces the total lifetime costs [2]. Benefits have been demonstrated in terms of decreased risk of cardiovascular diseases (CVD) [4][5][6], obesity [7], metabolic syndrome [8,9] and type-2 diabetes [10-13], as well as of certain types of neurodegenerative diseases and late-life cognitive disorders [14-17] and cancers [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The protective role of MD on multiple health outcomes has been widely demonstrated (43). Moreover, the adoption of this pattern is associated with other healthy habits such as having an active lifestyle and not smoking (44).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of foods and the content of nutrient constituents made the Mediterranean diet a subject of many scientific studies, that investigated the potential health effect during the intervention by Mediterranean eating (reviewed by Sofi, Macchi, Abbate, Gensini & Casini, 2014;Martinez-Lacoba et al, 2018). An early systematic review by Serra-Majem, Roman and Estruch (2006) investigated 35 experimental studies referring to the Mediterranean diet as an intervention and showed favourable effects on lipoprotein levels, endothelium-dependent vasodilatation, insulin resistance, metabolic syndrome, antioxidant capacity, myocardial and cardiovascular mortality, and cancer incidence.…”
Section: Mediterranean Diet-induced Health Effectsmentioning
confidence: 99%
“…From their work, the foundation of the concept of Mediterranean diet and lifestyles were set (Keys et al, 1986). Unfortunately, in those countries, 60 years later, the traditional way of eating and the healthy lifestyles have been cancelled, to a great extent due to homogenization of dietary choices and living habits typical of the global economy (Bach-Faig et al, 2011;Martinez-Lacoba, Pardo-Garcia, Amo-Saus & Escribano-Sotos, 2018).…”
Section: Introductionmentioning
confidence: 99%